Assessing aspects of better birth initiatives: a single centre experience - Nwafor, Amuche V.; Umeora, Odidika U.; Ikeotuonye, Arinze C.; Obi, Vitus O.; Adiele, Nnabugwu A.; Iwe, Bobby; Okoroafor, Francis C.; Obi, Chuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Better birth initiative is a global initiative that promotes humane and evidence-based care for women during childbirth. This study was designed to assess compliance to aspects of better birth initiative and maternal satisfaction with a view to making recommendations. Methods: This study was a descriptive cross-sectional study of 396 consenting post-partum women to assess maternity services at AEFUTHA. A sample size of 423 was determined at power of 90% and α-error of 0.05. Data was analyzed using SPSS version 22. Chi-square was used to analyze categorical variables and odds ratios determined. Continuous variables were expressed as mean or standard deviation. P value of <0.05 was taken to be statistically significant. Results: Out of a total of 423 questionnaires deployed, only 396 were completed and duly returned (giving a 93.6% response rate). Majority of the parturient were between the ages of 20 to 34 years (80.3%), multiparas (74.2%) and with tertiary education (74.2%). Although many (74.2%) were not allowed companions, free mobility (78.8%), food (70.7%) and position of choice in labour (100%), they were satisfied with the care. Factors that likely affected maternal satisfaction were the age of participants, having a companion in labour, having a dedicated midwife to each parturient, free mobility in labour, oral fluid intake in labour and good health worker attitude (p value: 0.002, 0.024, 0.002, 0.0002, 0.0001 and 0.00001 respectively). Conclusions: There is need to continuously enlighten health professionals on aspects of better birth initiatives in order to improve client’s satisfaction.